1986
DOI: 10.1016/0014-5793(86)81489-2
|View full text |Cite
|
Sign up to set email alerts
|

3′‐Hydroxymethyl 2′‐deoxynucleoside 5′‐triphosphates are inhibitors highly specific for reverse transcriptase

Abstract: dNTP(3′‐OCH3), a 3′‐O‐methyl derivative of dNTP, is a chain terminator substrate for DNA synthesis catalyzed by AMV reverse transriptase. The enzyme seems to be the only DNA polymerase susceptible to the inhibitor while all the other DNA polymerases tested are fully resistant to the nucleotide analog. The resistant polymerases are: E. coli DNA polymerase I, Klenow's fragment of DNA polymerase I, phage T4 DNA polymerase, calf thymus DNA polymerase α, rat liver DNA polymerase β and calf thymus terminal deoxyribo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 12 publications
1
23
0
Order By: Relevance
“…The results reported here may indicate that the polymerase-bound 3' end of DNA lies in the vicinity of a powerful nucleophilic group in the active site involved either in polymerization or in 3'-substituent removal, a finding in accordance with crystallographic data for several DNA polymerases (8)(9)(10)(11)(12). "Readthrough" (16), "quenching" (18), and results reported by others (23,26,27) may be explained by a quantitative removal of the fluorescent reporter upon enzymatic chain extension.…”
Section: Discussionsupporting
confidence: 77%
“…The results reported here may indicate that the polymerase-bound 3' end of DNA lies in the vicinity of a powerful nucleophilic group in the active site involved either in polymerization or in 3'-substituent removal, a finding in accordance with crystallographic data for several DNA polymerases (8)(9)(10)(11)(12). "Readthrough" (16), "quenching" (18), and results reported by others (23,26,27) may be explained by a quantitative removal of the fluorescent reporter upon enzymatic chain extension.…”
Section: Discussionsupporting
confidence: 77%
“…The 17-member oligonucleotide d(GTAAAACCACGGCCAGT) and the 14-member d(CCCAGTCACGACGT) were labeled with [32p] at the 5'-position using polynucleotide kinase and [7-32p]ATP. dNTP(3'-NH2) and dNTP(3'-N3) [10], dNTP(3'-F) Jill dNTP(3'-OCH3) [12], araNTP(3'-N3) and ara-NTP(3'-NH2) [13] were synthesized as described.…”
Section: Methodsmentioning
confidence: 99%
“…From tracks 4-5 it can be seen that dddTTP terminates DNA chain elongation catalyzed by AMV reverse transcriptase, the effectiveness of this process being significantly greater than that in control tracks. For these control tracks, termination was achieved with dNTP(3'-OCH3) (tracks 2,3) [12]. Strong termination of DNA synthesis in the presence of dddTTP is observed in a set of bands with shorter DNA fragments (the fragments that terminated on 8T, 9T, 14T, 20T, 25T, 27T, 34T) in comparison with DNA fragments in tracks 2 and 3.…”
Section: Data Polymerase I Kf From E Coli Amvmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that nucleotides with ether linkages at the 3Ј position can be incorporated by some DNA polymerases, whereas those with ester linkages are not generally accepted by most of the polymerases tested (18). Significant efforts have been dedicated to evaluating a wide variety of 3Ј-modified nucleotides to be used as terminators for various DNA polymerases and reverse transcriptases, but none of the functional groups tested have had established methods to regenerate a free 3Ј-OH (19)(20)(21)(22).…”
mentioning
confidence: 99%